Lean Approach to Minimize Waste in Biscuit Production Process Using Value Stream Mapping Method at PT. XYZ - Lubis, Dinda Agustina; Pujangkoro, Sugiharto; Hidayati, Juliza (Jurnal Sistem Teknik Industri, 2024)
PT XYZ is one of the companies in the snack food industry that focuses on processing biscuits. There is still waste in the production process, such as waiting and transportation, which adds time to the production process and makes it longer. To reduce waste and improve business efficiency, this research uses lean methodology and value stream mapping to ensure the biscuit processing production process runs smoothly. The results of the research that has been done, there is a decrease in non-value-added time by 13.27 minutes from 22.77 minutes, a total lead time of 68.32 minutes from 77.82 minutes, and process cycle efficiency increased by 75.29% from 66.10%. This shows that implementing lean methods using value stream mapping can improve the company's efficiency and productivity.